Peluang Dan Ancaman Kerja Sama Di Sektor Energi Dan Kebijakan Untuk Mengatasinya: Studi Kasus Indonesia dengan Singapura - Asep Awaludin; Dian Nur Fitriyani; Ragil Setyorini; Yulia Nurfazrin; Daspar (Jurnal Ekonomi dan Bisnis Digital, 2024)
In recent years, economic relations between Indonesia and Singapore have become warmer. Singapore is still one of Indonesia's main economic partners in investment and trade. The two countries also benefit jointly from industrial cooperation in Indonesia, such as SEZs (Special Economic Zones), namely Nongsa Digital Park on Batam Island, Riau Islands, and Kendal Industrial Estate in Central Java. In 2021, three large-scale power plant projects were signed by a joint venture of Indonesia and Singapore, to accelerate the development of the renewable energy industry in Batam. The three projects will provide benefits for each country. Due to limited land, Singapore cannot build large-scale solar power plants. Meanwhile, Indonesia has abundant natural resources and is also located in a strategic geographical position. Thus, cooperation between the two countries will encourage the transition of renewable energy, as well as create new quality jobs in Batam.